The Influence of Islamicity Performance Index and Liquidity Through Intellectual Capital on the Financial Performance of Islamic Commercial Bank - Faizal, Ilham; Prasetyowati, Riris Aishah (Wealth: Journal of Islamic Banking and Finance, 2023)
This study aims to analyze the influence of Islamicity Performance Index and Liquidity Through Intellectual Capital on the Financial Performance of Islamic Commercial Banks. The type of data used in this study is panel data, namely quarterly from 2019 to 2021 and using samples of 5 (five) Sharia Commercial Banks with Purposive Sampling techniques as the sampling technique used in this study. The analysis method used in this study is panel data regression analysis and Path analysis using Eviews 10.0 and Microsoft excel 2016 software. The results in this study show that the Islamicity Performance Index has a significant effect on Intellectual Capital. Liquidity has a significant effect on Intellectual Capital. Islamicity Performance Index has a significant effect on Return On Assets. Liquidity has a significant effect on Return On Assets. Intellectual Capital does not have a significant effect on Return On Assets. Meanwhile, simultaneously the Islamicity Performance Index and liquidity have a significant effect on Intellectual Capital. Islamicity Performance Index, liquidity, and Intellectual Capital have a significant effect on Return On Assets.